Sequential Deposition of Donor and Acceptor Provides High‐Performance Semitransparent Organic Photovoltaics Having a Pseudo p–i–n Active Layer Structure. Issue 13 (29th January 2021) - Wang, Hao‐Cheng; Cheng, Pei; Tan, Shaun; Chen, Chung‐Hao; Chang, Bin; Tsao, Cheng‐Si; Chen, Li‐Yin; Hsieh, Chung‐An; Lin, Yu‐Che; Cheng, Hao‐Wen; Yang, Yang; Wei, Kung‐Hwa
Abstract: Semitransparent organic photovoltaics (ST‐OPVs) have great potential for use in renewable energy technologies. In bulk‐heterojunction (BHJ) ST‐OPVs, a compromise is necessary between the visible light transmittance (VLT) and the power conversion efficiency (PCE). A sequential deposition (SD) strategy that involves individually depositing a polymer donor layer (D) and a small‐molecule acceptor layer (A) as the active layer is presented; where molecular diffusion occurring at the interfacial region results in a pseudo p–i–n structure. PBDB‐T‐2F(D)/Y6(A) ST‐OPVs are fabricated with different active layer thicknesses—at 115 nm, the SD (D:A/75:40 nm) and BHJ devices (D:A/1:1.2 w) provide the champion PCE of 12.91% (VLT of 14.5%) and 12.77% (VLT of 13.4%), respectively; at 85 nm, the SD (D:A/45:40 nm) and BHJ devices (D:A/1:1.2 w) provide a PCE of 12.22% (VLT of 22.2%) and 11.23% (VLT of 16.6%), respectively. This trend indicates SD devices have larger PCE and VLT values than the BHJ devices at a given active layer thickness, and the enhancements of PCE and VLT values by the SD structures against the BHJ structures become more pronounced as the active layer thickness reduced. The SD strategy provides a new approach for achieving ST‐OPVs with both high efficiency and high transparency. Abstract : In typical semitransparent organic photovoltaics (ST‐OPVs) that incorporate bulk heterojunction (BHJ) active layers, a compromise is made between the visible light transmittance (VLT) and power conversion efficiency (PCE). A new strategy with a sequential‐deposition (SD) active layer involving pseudo p–i–n structures provides ST‐OPVs with simultaneously higher PCE and VLT than that of the BHJ devices at the same layer thickness.